Professores iniciantes: como compreendem o seu trabalho? - Lotumolo, Thais Elena (2014)
This research aims to understand which the perceptions and senses attributed by beginner teachers developing their professional career in school organizations are. The research was conducted in Hortolândia city, in São Paulo, and therefore, it was made interviews with teachers belonging to the municipal public schools network of the pictured locality. It is considered that the beginning stage of teaching is a specific moment in educators career, since it is a period that involves adversities, doubts and joy. Therefore, this concerning moment in beginner teachers career must be taken into consideration, offering support to the initial journey of teaching. Through data collection and their analyses, this work reports the necessities of the beginner teachers, as well as their educational experiences. The adopted methodology involves the interviews content analysis, that is, it was considered the speech and the narrative offered by the beginner teachers. In that sense, it is important to stand out the relation between the beginner teachers aspirations and the support offered in the educational environment. The presented study seeks to reveal the importance of focusing on the initial stage of teaching, on building new postures and on attitudes that meet the perceptions of the beginner teacher.